2017Depression after Stroke in Sub-Saharan Africa: A Systematic Review and Meta-Analysis (2017)
Objective. We aimed to conduct a systematic review and meta-analysis of prevalence and characteristics of poststroke depression (PSD) in sub-Saharan Africa (SSA). Methods. We searched Medline, PsycINFO, and African Journals OnLine using keywords for stroke and depression and the .mp. operator for all 54 SSA countries/regions. Further information was retrieved through a manual search of references from relevant published and unpublished articles. We included only peer-reviewed original studies with epidemiological or experimental designs, conducted random-effect meta-analysis, and identified the most commonly associated factors by weight (inverse of variance method). Results. Seventeen studies, comprising 1483 stroke survivors, met the criteria for syntheses. The pooled frequency of clinically diagnosed PSD was 31% (95% CI = 26%–36%), versus 13.9% in healthy control pairs. Prevalence did not vary much across healthcare settings but was affected by methods of depression ascertainment. PSD was significantly associated with low education, cognitive impairment, physical disability, poor quality of life, and divorced marital status. Conclusion. Almost 1 in 3 individuals with stroke in SSA has clinical depression. Despite limitations around quality of identified studies, results of the present systematic review overlap with findings in the global literature and highlight useful targets for the design and trial of tailored intervention for PSD in SSA